2023
DOI: 10.5501/wjv.v12.i4.221
|View full text |Cite
|
Sign up to set email alerts
|

Association between alcohol-associated cirrhosis and inpatient complications among COVID-19 patients: A propensity-matched analysis from the United States

Faisal Inayat,
Hassam Ali,
Pratik Patel
et al.

Abstract: BACKGROUND Alcohol-associated cirrhosis (AC) contributes to significant liver-related mortality in the United States. It is known to cause immune dysfunction and coagulation abnormalities. Patients with comorbid conditions like AC are at risk of worse clinical outcomes from coronavirus disease 2019 (COVID-19). The specific association between AC and COVID-19 mortality remains inconclusive, given the lack of robust clinical evidence from prior studies. AIM To study the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The study of 1325 patients with ALC and confirmed COVID-19 compared to 1135 matched infected individuals without liver disease did not show ALC to be a factor increasing mortality in the course of SARS-CoV-2 infection. Nevertheless, cirrhotic patients presented a notably greater number of underlying complications (e.g., septic shock, upper extremity venous thromboembolism or atrial fibrillation) [258,259]. Other researchers found a positive association between decompensation of CLD and in-hospital mortality in COVID-19 patients.…”
Section: Characteristic Features Of Ald Patients In the Scope Of Covi...mentioning
confidence: 99%
“…The study of 1325 patients with ALC and confirmed COVID-19 compared to 1135 matched infected individuals without liver disease did not show ALC to be a factor increasing mortality in the course of SARS-CoV-2 infection. Nevertheless, cirrhotic patients presented a notably greater number of underlying complications (e.g., septic shock, upper extremity venous thromboembolism or atrial fibrillation) [258,259]. Other researchers found a positive association between decompensation of CLD and in-hospital mortality in COVID-19 patients.…”
Section: Characteristic Features Of Ald Patients In the Scope Of Covi...mentioning
confidence: 99%
“…Prior studies have shown that COVID-19 infection may cause acute liver injury that has been linked to increased mortality[ 16 - 19 ]. Moreover, patients with chronic liver disease and cirrhosis also have higher rates of healthcare utilization, morbidity, and mortality from COVID-19[ 20 - 22 ]. However, existing clinical evidence has not consistently shown worse clinical outcomes in LT recipients[ 23 ].…”
Section: Introductionmentioning
confidence: 99%